Abdominal aortic aneurysm as an IgG4‐related disease. (14th May 2019) - Prucha, M.; Sedivy, P.; Stadler, P.; Zdrahal, P.; Prokopova, P.; Voska, L.; Sedlackova, L.
Summary: The objectives of this study were to evaluate patients with aortic abdominal aneurysm (AAA) with regard to immunoglobulin (Ig)G4‐related disease (IgG4‐RD). IgG4‐RD represents a recently defined condition comprised of a collection of disorders characterized by IgG4 hypergammaglobulinemia, the presence of IgG4‐positive plasma cells in organs affected with fibrotic or sclerotizing changes and typical histopathological features. It was identified as a possible cause of vasculitis in large vessels. Studies have been published on a possible association between inflammatory aortic or cardiovascular disease and IgG4‐RD. We examined 114 patients with AAA requiring surgery in order to identify findings which are characteristic of IgG4‐RD. Aneurysm samples from seven patients showed histopathological features consistent with IgG4‐RD and the presence of IgG4 + plasma cells. Only two of these seven patients showed elevated IgG4 serum levels higher 1·35 g/l. In five of the patients, the concentration of serum IgG4 was lower than 1·20 g/l, with the number of IgG4 + plasma cells being higher than 50/high‐power field. These findings were consistent with AAA being a heterogeneous group of inflammatory diseases with different pathogenesis. Abstract : Aortic abdominal aneurysm is a heterogeneous group of inflammatory diseases with different pathogenesis. Some patients with AAA meet the criteria of IgG4‐RD. IgG4 levels are not a good predictive marker in patients with AAA for identifying patients with IgG4‐RD.